2016
DOI: 10.18632/oncotarget.14289
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte-to-monocyte ratio is associated with prognosis of diffuse large B-cell lymphoma: correlation with CD163 positive M2 type tumor-associated macrophages, not PD-1 positive tumor-infiltrating lymphocytes

Abstract: The research aims to examine the prognostic value of the lymphocyte-to-monocyte ratio (LMR), neutrophil-to- lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) in diffuse large B-cell lymphoma (DLBCL). The relation of these hematologic indicators to poor antitumor immunity and prognosis must be investigated. Clinicopathologic data and survival information of 355 patients with DLBCL was retrospectively analyzed. Univariate analysis revealed that lower LMR (<2.71), higher NLR (≥2.81), CD163+ M2 tumor-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 42 publications
3
68
1
Order By: Relevance
“…Our findings may suggest that IL-34 is one such factor because IL-34, which induces the migration of monocytic cells, is often expressed in the DLBCL lymphoma tissues. [27][28][29][30][31][32][33][34][35][36] In this study, we showed that the total number of macrophages, that is Iba-1 + macrophages, in the lymphoma tissues of IL-34 + DLBCL patients who showed shorter survival periods, was significantly higher than that of IL-34 À patients ( Figure 4). In this study, we also revealed that IL-34 induces cell migration even at high concentrations unlike M-CSF (Figure 5a, b).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Our findings may suggest that IL-34 is one such factor because IL-34, which induces the migration of monocytic cells, is often expressed in the DLBCL lymphoma tissues. [27][28][29][30][31][32][33][34][35][36] In this study, we showed that the total number of macrophages, that is Iba-1 + macrophages, in the lymphoma tissues of IL-34 + DLBCL patients who showed shorter survival periods, was significantly higher than that of IL-34 À patients ( Figure 4). In this study, we also revealed that IL-34 induces cell migration even at high concentrations unlike M-CSF (Figure 5a, b).…”
Section: Discussionmentioning
confidence: 85%
“…[27][28][29][30][31] The survival periods of patients with higher number of macrophages in lymphoma tissues tended to be shorter than those of patients with lower number of macrophages (Supplementary figure 6), although the difference was not statistically significant, presumably because of a small sample size (n = 53). Nevertheless, our results are consistent with several studies demonstrating that the number of tumor-infiltrating macrophages correlates with the poor prognosis of patients with DLBCL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have demonstrated a significant reduction in morbidity, from 53% to 19% over two decades, with a concomitant reduction in mortality from 5.2% to 1.6% at 90 days post-operatively. [19][20][21][22] Theoretically, a low LMR could be correlated with adverse outcomes. Currently, detection methods for post-operative complications include, but are not limited to, monitoring serum haematological and biochemical parameters, cross-sectional imaging, clinical examination and drain output.…”
Section: Introductionmentioning
confidence: 99%